Blue rubber bleb nevus syndrome - ERTEM ŞAHİNOĞLU, DENİZ (AMER ACAD PEDIATRICS, 2001)
Blue rubber bleb nevus syndrome is a rare disorder characterized by distinctive cutaneous and gastrointestinal venous malformations that usually cause massive or occult gastrointestinal hemorrhage and iron deficiency anemia secondary to the bleeding episodes. It is even a rare cause of gastrointestinal hemorrhage during childhood. We describe a 6-year-old boy who had multiple venous malformations all over his body. He also suffered from several episodes of melena, chronic anemia, and growth retardation. The endoscopic examination of the gastrointestinal tract revealed multiple bluish-black sessile and polypoid venous malformations in various sizes. It was possible to remove the largest venous malformations causing massive bleeding during colonoscopy.
Keywords: venous malformations; child; HEMANGIOMAS; INVOLVEMENT